Preparation method of high-thermal-conductivity silicon nitride ceramic material for lightning protection insulator

By synthesizing silicon nitride composite powders with modified β-silicon nitride whiskers and other raw materials, and using cold isostatic molding and pneumatic sintering methods, the problems of low thermal conductivity and poor thermal shock resistance of existing materials are solved, and the preparation of silicon nitride ceramic materials with high thermal conductivity and strength properties are achieved.

CN119899044AActive Publication Date: 2025-04-29SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510386650.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-29
Estimated Expiration
2045-03-31

AI Technical Summary

Technical Problem

The existing high-aluminum ceramic materials have low thermal conductivity and poor thermal shock resistance in lightning protection insulators, which cannot meet the needs of rapid heat dissipation. At the same time, the thermal conductivity of silicon nitride ceramics prepared by air pressure sintering is generally low.

Method used

β-Si3N4 whiskers are used as templates to prepare modified β-silicon nitride whiskers and synthesize silicon nitride composite powders with other raw materials. The thermal conductivity and strength properties of silicon nitride ceramics are improved by cold isostatic molding and pneumatic sintering.

Benefits of technology

It significantly improves the thermal conductivity, bending strength, fracture toughness and density of silicon nitride ceramics, meeting the needs of rapid heat dissipation of lightning protection insulators.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-thermal-conductivity silicon nitride ceramic material for a lightning protection insulator, and belongs to the technical field of silicon nitride ceramics, the method comprises the following steps: preparing beta-silicon nitride whiskers, modifying the beta-silicon nitride whiskers, preparing silicon nitride composite powder, performing cold isostatic pressing, and performing air pressure sintering; the beta-silicon nitride whisker modification method comprises the following steps: dispersing beta-silicon nitride whiskers in a hydrolyzed and activated polyacrylamide solution, adding a dehydrating agent N, N-dicyclohexylcarbodiimide, reacting at 50-60 DEG C for 2-3 hours, filtering and separating a product after the reaction is finished, washing with water, and drying to obtain the modified beta-silicon nitride whiskers. According to the silicon nitride ceramic prepared by the method disclosed by the invention, the thermal conductivity is 87.5 to 89.2 W / (m.K), the bending strength is 837 to 850 MPa, the fracture toughness is 10.6 to 11.1 MPa.m < 1 / 2 >, and the density is 3.09 to 3.21 g / cm < 3 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicon nitride ceramics, and in particular relates to a method for preparing a high thermal conductivity silicon nitride ceramic material for a lightning protection insulator. Background Art

[0002] Lightning protection insulators are key components in communication systems that combine lightning protection and insulation support functions. In order to prevent the large current generated by direct lightning strikes from passing through the communication antenna to damage the back-end equipment, communication antenna insulators are currently required to have integrated lightning protection functions. During a lightning strike, a large amount of lightning energy accumulates inside the insulator, resulting in heat accumulation and temperature increase. This requires that the lightning protection insulator can quickly dissipate heat and reduce the damage to electronic components in the lightning discharge channel. The material used in existing antenna insulators is mainly high-aluminum porcelain. Although high-aluminum porcelain materials have the advantages of high temperature resistance, high insulation, corrosion resistance, wear resistance, and high strength, they have poor thermal shock resistance, low thermal conductivity, and slow heat dissipation, which cannot meet the use requirements.

[0003] In order to solve the inherent defects of high-alumina ceramics, high-performance ceramic materials represented by silicon nitride (Si3N4) ceramics have become the preferred direction for upgrading lightning protection insulators in recent years due to their ultra-high thermal conductivity and excellent thermal shock resistance. Existing high-thermal conductivity silicon nitride ceramics are mostly prepared by hot pressing and sintering. The uniaxial pressure of hot pressing and sintering causes the β-Si3N4 grains to grow directional along the pressure direction, resulting in a small number of grain boundaries, low phonon scattering rate, and high thermal conductivity. However, this hot pressing and sintering method is only suitable for forming simple geometric shapes. It is difficult to achieve uniform pressing and forming for complex and irregular structures such as lightning protection insulators. Gas pressure sintering can sinter various irregular silicon nitride ceramics, but the grains of gas phase sintering are randomly oriented, the phonon conduction path is blocked, and the thermal conductivity is generally low.

[0004] In order to improve the thermal conductivity of silicon nitride ceramic materials prepared by gas pressure sintering, the prior art uses β-Si3N4 whiskers as a template to guide the growth of grains along a specific direction, reduce the number of grain boundaries, and improve thermal conductivity.

[0005] CN112573936A discloses a method for preparing a silicon nitride ceramic substrate, comprising the following steps: step S1, rolling α-Si3N4 powder, β-Si3N4 whiskers, h-BN powder, sintering aids and binders to prepare a sheet-like body with oriented β-Si3N4 whiskers; step S2, degreasing the sheet-like body to obtain a degreased body; step S3, gas pressure sintering the degreased body to make α-Si3N4 undergo phase change under the induction of β-Si3N4 whiskers and promote the oriented growth of β-Si3N4 grains, so as to prepare a silicon nitride ceramic substrate with oriented β-Si3N4 rod-shaped grains. The use of β-Si3N4 whiskers as seeds in this patent can promote nucleation, increase growth driving force, and also act as a template to guide the growth of grains in a specific direction, increase density, reduce lattice oxygen defects, and increase thermal conductivity. However, as a high aspect ratio material, the ball milling mixing method used in the mixing process of β-Si3N4 whiskers can easily destroy the structure of the β-Si3N4 whiskers, and the mixing uniformity is poor, making it difficult to improve thermal conductivity and increase strength. Therefore, in the raw material powder of silicon nitride ceramics, protecting the β-Si3N4 whisker structure from being destroyed, improving the uniformity of the raw material mixing, and improving the thermal conductivity of silicon nitride ceramics under gas pressure sintering are problems that need to be urgently solved in the prior art. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators, which improves the thermal conductivity of silicon nitride ceramics and increases the bending strength, fracture toughness and density of silicon nitride ceramics.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a high thermal conductivity silicon nitride ceramic material for a lightning protection insulator comprises the following steps: preparing β-silicon nitride whiskers, modifying the β-silicon nitride whiskers, preparing silicon nitride composite powder, cold isostatic pressing, and gas pressure sintering; The method for preparing β-silicon nitride whiskers comprises: using silicon powder and α-Si3N4 as raw materials, and Y2O3 as an auxiliary agent, uniformly mixing the raw materials and the auxiliary agent, sintering the raw materials in a N2 atmosphere at 3-5MPa and 1700-1800°C for 1-1.5h, soaking the sintered material in a hydrofluoric acid solution for 10-15min, washing with water and drying after the soaking, and obtaining β-silicon nitride whiskers; The mass ratio of silicon powder, α-Si3N4 and Y2O3 is 70-80:20-30:2.5-3; The particle size of the silicon powder is 300-500nm; The particle size of the α-Si3N4 is 500-800nm; The concentration of the hydrofluoric acid solution is 5-10wt%.

[0008] The method for modifying the β-silicon nitride whiskers is as follows: dispersing the β-silicon nitride whiskers in a hydrolysis-activated polyacrylamide solution, adding a dehydrating agent N,N-dicyclohexylcarbodiimide, reacting at 50-60° C. for 2-3 hours, filtering and separating the product after the reaction, washing with water, and drying to obtain the modified β-silicon nitride whiskers; The mass ratio of the β-silicon nitride whisker, the hydrolysis-activated polyacrylamide solution, and the N,N-dicyclohexylcarbodiimide is 10:50-70:0.2-0.4; The preparation method of the hydrolysis-activated polyacrylamide solution comprises dissolving polyacrylamide in water to prepare a polyacrylamide solution, dripping a NaOH solution into the polyacrylamide solution under stirring, stopping the dripping when the pH value of the solution reaches 10-11, heating the mixed solution to 60-80° C., stirring and reacting for 1-2 hours at a constant temperature, and controlling the pH range of the solution to be 10-11 during the reaction, and obtaining a hydrolysis-activated polyacrylamide solution after the reaction is completed; The number average molecular weight of the polyacrylamide is 1.06-2.11 million; The concentration of the polyacrylamide solution is 5-8wt%; The concentration of the NaOH solution is 20-30 g / L.

[0009] The method for preparing the silicon nitride composite powder comprises: dissolving methacrylamide in water, then adding α-Si3N4 powder, Y2O3, MgSiN2 and a dispersant, performing a first ultrasonic dispersion for 10-15 minutes to obtain a premixed liquid, then adding the modified β-silicon nitride whisker to the premixed liquid under stirring, performing a second ultrasonic dispersion for 20-30 minutes, drying at 60-80° C. for 4-6 hours to obtain a gel, and calcining the gel at 500-600° C. in a nitrogen atmosphere for 2-3 hours to obtain the silicon nitride composite powder; The mass ratio of water, methacrylamide, α-Si3N4 powder, Y2O3, MgSiN2, dispersant, and modified β-silicon nitride whisker is 100:8-10:100-120:3-4:3-4:0.6-1:6-8; The dispersant is one of sodium polyacrylate and polyvinyl alcohol; The frequency of the primary ultrasound is 50-70kHz; The frequency of the secondary ultrasound is 20-30 kHz.

[0010] The cold isostatic pressing method comprises pressing the silicon nitride composite powder at a pressure of 110-130 MPa for 30-35 minutes to obtain a silicon nitride ceramic blank.

[0011] The gas pressure sintering method is to put the silicon nitride ceramic blank into a gas pressure sintering furnace, and sinter it in a nitrogen atmosphere of 1800-1900° C. and 3-4 MPa to obtain a high thermal conductivity silicon nitride ceramic.

[0012] Compared with the prior art, the present invention has the following beneficial effects: 1. The method for preparing high thermal conductivity silicon nitride ceramics of the present invention uses β-silicon nitride whiskers as seeds to provide nucleation points and promote the transformation of α-silicon nitride to β-silicon nitride. At the same time, the added β-silicon nitride whiskers can also improve the bending strength and fracture toughness of silicon nitride ceramics. In the preparation step of β-silicon nitride whiskers, after the fired material is soaked in a hydrofluoric acid solution, a single whisker can be separated from the staggered growing whiskers, and the whisker surface can be etched to a certain extent. The β-silicon nitride whiskers are modified and fired in the preparation of silicon nitride composite powder, and the etched surface of the silicon nitride whiskers is not destroyed. During the sintering process of preparing silicon nitride ceramics, the etched surface can provide more nucleation points for the β-silicon nitride whiskers as seeds, promoting the densification process during the sintering process. Reduce porosity and increase the density of silicon nitride ceramics, thereby improving the thermal conductivity and strength properties of silicon nitride ceramics; β-silicon nitride whiskers have a high aspect ratio and can act as a template to guide the growth of grains in a specific direction, forming a more uniform microstructure, which helps to improve the thermal conductivity, bending strength and fracture toughness of silicon nitride ceramics; a more uniform grain-dense growth structure can reduce lattice oxygen defects, and the long strip structure of β-silicon nitride whiskers helps to form a more effective heat conduction path, thereby improving the thermal conductivity of the material.

[0013] 2. The method for preparing high thermal conductivity silicon nitride ceramics of the present invention can improve the thermal conductivity, flexural strength, fracture toughness and density of silicon nitride ceramics. The thermal conductivity of high thermal conductivity silicon nitride ceramics prepared by the method of the present invention is 87.5-89.2W / (m·K), the flexural strength is 837-850MPa, and the fracture toughness is 10.6-11.1MPa·m 1 / 2 , density is 3.09-3.21g / cm 3 . DETAILED DESCRIPTION

[0014] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0015] Example 1 A method for preparing a high thermal conductivity silicon nitride ceramic material for a lightning protection insulator is as follows: (1) Preparation of β-silicon nitride whiskers 70g of silicon powder, 30g of α-Si3N4 and 2.5g of Y2O3 were uniformly mixed, and fired for 1h in a N2 atmosphere at 3MPa and 1800℃, and then the fired material was placed in a hydrofluoric acid solution and soaked for 10min. After the soaking was completed, the product was filtered and separated, washed with water and dried to obtain β-silicon nitride whiskers; The particle size of the silicon powder is 300 nm; The particle size of the α-Si3N4 is 500nm; The concentration of the hydrofluoric acid solution is 10 wt %.

[0016] (2) β-Silicon Nitride Whiskers Modification Disperse 10 g of β-silicon nitride whiskers in 50 g of hydrolyzed activated polyacrylamide solution, add 0.2 g of N,N-dicyclohexylcarbodiimide, react at 50° C. for 3 h, and after the reaction is completed, filter and separate the product, wash with water, and dry to obtain modified β-silicon nitride whiskers; The preparation method of the hydrolysis-activated polyacrylamide solution comprises the following steps: dissolving polyacrylamide in water to prepare a polyacrylamide solution with a concentration of 5wt%, dripping a NaOH solution with a concentration of 20g / L into the polyacrylamide solution under stirring, stopping the dripping when the pH value of the solution reaches 10, heating the mixed solution to 60°C, stirring and reacting at a constant temperature for 2h, controlling the pH value of the solution to be 10 during the reaction, and obtaining the hydrolysis-activated polyacrylamide solution after the reaction is completed.

[0017] (3) Preparation of silicon nitride composite powder 8 g of methacrylamide was dissolved in 100 g of water, and then 100 g of α-Si3N4 powder, 3 g of Y2O3, 3 g of MgSiN2, and 0.6 g of sodium polyacrylate were added, and ultrasonic dispersion was performed at a frequency of 50 kHz for 15 min to obtain a premixed solution, and then 6 g of modified β-silicon nitride whiskers were added to the premixed solution under stirring, and ultrasonic dispersion was performed at a frequency of 20 kHz for 30 min, and dried at 60° C. for 6 h to obtain a gel, and the gel was sintered at 500° C. in a nitrogen atmosphere for 3 h to obtain a silicon nitride composite powder; The number average molecular weight of the polyacrylamide is 1.06 million.

[0018] (4) Cold isostatic pressing The silicon nitride composite powder was pressed at a pressure of 110 MPa for 30 minutes to obtain a silicon nitride ceramic blank of 50×40×20 mm.

[0019] (5) Gas pressure sintering The silicon nitride ceramic blank is sent into a gas pressure sintering furnace and sintered in a nitrogen atmosphere at 1800° C. and 4 MPa to obtain a high thermal conductivity silicon nitride ceramic.

[0020] Example 2 A method for preparing a high thermal conductivity silicon nitride ceramic material for a lightning protection insulator is as follows: (1) Preparation of β-silicon nitride whiskers 75g of silicon powder, 25g of α-Si3N4 and 2.7g of Y2O3 were uniformly mixed, and fired for 1.2h in a N2 atmosphere at 4MPa and 1750℃, and then the fired material was immersed in a hydrofluoric acid solution for 12min. After the immersion, the product was separated by filtration, washed with water and dried to obtain β-silicon nitride whiskers; The particle size of the silicon powder is 400 nm; The particle size of the α-Si3N4 is 600nm; The concentration of the hydrofluoric acid solution is 8 wt %.

[0021] (2) β-Silicon Nitride Whiskers Modification Disperse 10 g of β-silicon nitride whiskers in 60 g of hydrolyzed activated polyacrylamide solution, add 0.3 g of N,N-dicyclohexylcarbodiimide, react at 55° C. for 2.5 h, and after the reaction is completed, filter and separate the product, wash with water, and dry to obtain modified β-silicon nitride whiskers; The preparation method of the hydrolysis-activated polyacrylamide solution comprises dissolving polyacrylamide in water to prepare a polyacrylamide solution with a concentration of 6 wt %, dripping a NaOH solution with a concentration of 25 g / L into the polyacrylamide solution under stirring, stopping the dripping when the pH value of the solution reaches 10.5, heating the mixed solution to 70° C., stirring and reacting at a constant temperature for 1.5 hours, and controlling the pH value of the solution to be 10.5 during the reaction, and obtaining a hydrolysis-activated polyacrylamide solution after the reaction is completed; The number average molecular weight of the polyacrylamide is 1.54 million.

[0022] (3) Preparation of silicon nitride composite powder 9 g of methacrylamide was dissolved in 100 g of water, and then 110 g of α-Si3N4 powder, 3.5 g of Y2O3, 3.5 g of MgSiN2 and 0.7 g of sodium polyacrylate were added, and ultrasonic dispersion was performed at a frequency of 60 kHz for 12 min to obtain a premixed liquid. Then 7 g of modified β-silicon nitride whiskers were added to the premixed liquid under stirring, and ultrasonic dispersion was performed at a frequency of 25 kHz for 25 min. The premixed liquid was dried at 70°C for 5 h to obtain a gel, and the gel was sintered at 550°C in a nitrogen atmosphere for 2.5 h to obtain a silicon nitride composite powder.

[0023] (4) Cold isostatic pressing The silicon nitride composite powder was pressed at a pressure of 120 MPa for 32 minutes to obtain a silicon nitride ceramic blank of 50×40×20 mm.

[0024] (5) Gas pressure sintering The silicon nitride ceramic blank is sent into a gas pressure sintering furnace and sintered at 1850°C and 3.5MPa in a nitrogen atmosphere to obtain a high thermal conductivity silicon nitride ceramic.

[0025] Example 3 A method for preparing a high thermal conductivity silicon nitride ceramic material for a lightning protection insulator is as follows: (1) Preparation of β-silicon nitride whiskers 80g of silicon powder, 20g of α-Si3N4 and 3g of Y2O3 were uniformly mixed, and fired for 1.5h in a N2 atmosphere at 5MPa and 1700℃, and then the fired material was placed in a hydrofluoric acid solution and soaked for 15min. After the soaking was completed, the product was filtered and separated, washed with water and dried to obtain β-silicon nitride whiskers; The particle size of the silicon powder is 500nm; The particle size of the α-Si3N4 is 800nm; The concentration of the hydrofluoric acid solution is 5 wt %.

[0026] (2) β-Silicon Nitride Whiskers Modification Disperse 10 g of β-silicon nitride whiskers in 70 g of hydrolyzed activated polyacrylamide solution, add 0.4 g of N,N-dicyclohexylcarbodiimide, react at 60° C. for 2 h, filter and separate the product after the reaction, wash with water, and dry to obtain modified β-silicon nitride whiskers; The preparation method of the hydrolysis-activated polyacrylamide solution comprises dissolving polyacrylamide in water to prepare a polyacrylamide solution with a concentration of 8wt%, dripping a NaOH solution with a concentration of 30g / L into the polyacrylamide solution under stirring, stopping the dripping when the pH value of the solution reaches 11, heating the mixed solution to 80°C, stirring and reacting at a constant temperature for 1h, and controlling the pH value of the solution to be 11 during the reaction, and obtaining a hydrolysis-activated polyacrylamide solution after the reaction is completed; The number average molecular weight of the polyacrylamide is 2.11 million.

[0027] (3) Preparation of silicon nitride composite powder 10g of methacrylamide was dissolved in 100g of water, and then 120g of α-Si3N4 powder, 4g of Y2O3, 4g of MgSiN2 and 0.8g of polyvinyl alcohol were added, and ultrasonic dispersion was performed at a frequency of 70kHz for 10min to obtain a premixed liquid. Then 8g of modified β-silicon nitride whiskers were added to the premixed liquid under stirring, and ultrasonic dispersion was performed at a frequency of 30kHz for 20min. The premixed liquid was dried at 80°C for 4h to obtain a gel, and the gel was sintered at 600°C in a nitrogen atmosphere for 2h to obtain a silicon nitride composite powder.

[0028] (4) Cold isostatic pressing The silicon nitride composite powder was pressed at a pressure of 130 MPa for 35 minutes to obtain a silicon nitride ceramic blank of 50×40×20 mm.

[0029] (5) Gas pressure sintering The silicon nitride ceramic blank is sent into a gas pressure sintering furnace and sintered in a nitrogen atmosphere at 1900°C and 3MPa to obtain a high thermal conductivity silicon nitride ceramic.

[0030] Comparative Example 1 Comparative Example 1 adopts the preparation method of high thermal conductivity silicon nitride ceramics described in Example 2, except that the β-silicon nitride whisker modification step is omitted, and β-silicon nitride whiskers are used to replace modified β-silicon nitride whiskers in the step of preparing silicon nitride composite powder, and the remaining steps are the same.

[0031] Comparative Example 2 Comparative Example 2 adopts the preparation method of the high thermal conductivity silicon nitride ceramic described in Example 2, except that the β-silicon nitride whisker modification step is omitted, and the step of preparing the silicon nitride composite powder is changed to: 110g of α-Si3N4 powder, 3.5g of Y2O3, 3.5g of MgSiN2, 0.7g of sodium polyacrylate, and 7g of β-silicon nitride whiskers are added to 100g of ethanol, ball milled for 8h at a ball-to-material ratio of 6:1, the product is separated by filtration, and the silicon nitride composite powder is obtained after drying; The remaining steps are the same.

[0032] Test Example 1 The high thermal conductivity silicon nitride ceramic materials prepared by the methods of Examples 1-3 and Comparative Examples 1-2 were tested for thermal conductivity, flexural strength, fracture toughness and density, respectively. The thermal conductivity was tested by transient plane heat source method, the flexural strength was calculated by three-point bending method, the fracture toughness was tested by indentation method, and the density was tested by Archimedes drainage method. The test results are shown in Table 1.

[0033] Table 1 Thermal conductivity, flexural strength, fracture toughness and density of high thermal conductivity silicon nitride ceramic materials prepared in Examples 1-3 and Comparative Examples 1-2

[0034] It can be seen from Table 1 that the thermal conductivity, flexural strength, fracture toughness and density of the high thermal conductivity silicon nitride ceramics prepared by the methods of Examples 1-3 are all higher than those of Comparative Examples 1-2, indicating that the thermal conductivity, flexural strength, fracture toughness and density of the prepared silicon nitride ceramics can be improved by immersing the β-silicon nitride whiskers prepared by firing in a hydrofluoric acid solution, modifying the β-silicon nitride whiskers, and obtaining the silicon nitride composite powder by gel firing.

[0035] Modification of β-silicon nitride whiskers. After being immersed in a hydrofluoric acid solution, a certain amount of hydroxyl groups are introduced on the surface of the β-silicon nitride whiskers. The hydroxyl groups on the surface of the β-silicon nitride whiskers react with activated polyacrylamide to dehydrate and esterify, and polyacrylamide is grafted onto the surface of the β-silicon nitride whiskers, thereby introducing hydrophilic amide groups on the whisker surface, reducing the surface energy and increasing the hydrophilicity.

[0036] This change in surface properties makes the whiskers more easily surrounded by water molecules in water, reducing the interaction force between particles, thereby improving dispersibility; at the same time, the polyacrylamide molecular chain is relatively long, forming a dense protective layer on the surface of the whiskers, hindering the direct contact between the whisker particles, preventing the aggregation and sedimentation of the whisker particles, and improving the stability of the whisker suspension state. In the step of preparing silicon nitride composite powder, β-silicon nitride whiskers can be evenly dispersed in the premixed liquid to obtain a uniformly mixed silicon nitride composite powder. Silicon nitride ceramics made by pressing and molding the uniformly mixed silicon nitride composite powder and then sintering at high temperature have good thermal conductivity, bending strength, fracture toughness and density.

[0037] Comparative Example 1 omits the modification of β-silicon nitride whiskers, and directly uses β-silicon nitride whiskers and other raw materials to prepare silicon nitride composite powder. Due to the van der Waals force between the particles of the β-silicon nitride whiskers, the whiskers are easy to aggregate and difficult to maintain uniform dispersion. In addition, the surface energy of β-silicon nitride whiskers is relatively high, and they are easy to interact with other particles, causing agglomeration and sedimentation, and it is impossible to form a uniformly mixed silicon nitride composite powder, which in turn affects the thermal conductivity, strength properties and density of the silicon nitride ceramic.

[0038] Comparative Example 2 is relative to Example 2, and ball milling is used for mixing. During ball milling, the β-silicon nitride whiskers are destroyed, and whisker breakage or crushing occurs. The density of the prepared silicon nitride ceramic is reduced, and the orderliness of grain production is reduced, which affects the thermal conductivity, flexural strength, fracture toughness and density of the silicon nitride ceramic.

[0039] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators, characterized in that: The method comprises the following steps: preparing β-silicon nitride whiskers, modifying the β-silicon nitride whiskers, preparing silicon nitride composite powder, cold isostatic pressing, and gas pressure sintering; The method for modifying the β-silicon nitride whiskers is as follows: dispersing the β-silicon nitride whiskers in a hydrolysis-activated polyacrylamide solution, adding a dehydrating agent N,N-dicyclohexylcarbodiimide, reacting at 50-60° C. for 2-3 hours, filtering and separating the product after the reaction, washing with water, and drying to obtain the modified β-silicon nitride whiskers; The method for preparing the silicon nitride composite powder comprises the following steps: dissolving methacrylamide in water, then adding α-Si3N4 powder, Y2O3, MgSiN2 and a dispersant, performing a first ultrasonic dispersion for 10-15 minutes to obtain a premixed liquid, then adding the modified β-silicon nitride whisker to the premixed liquid under stirring, performing a second ultrasonic dispersion for 20-30 minutes, drying at 60-80°C for 4-6 hours to obtain a gel, and calcining the gel at 500-600°C in a nitrogen atmosphere for 2-3 hours to obtain the silicon nitride composite powder.

2. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 1, characterized in that: The method for preparing β-silicon nitride whiskers comprises: using silicon powder and α-Si3N4 as raw materials, and Y2O3 as an auxiliary agent, uniformly mixing the raw materials and the auxiliary agent, sintering them for 1-1.5 hours in a N2 atmosphere at 3-5MPa and 1700-1800°C, soaking the sintered material in a hydrofluoric acid solution for 10-15 minutes, and washing with water and drying after the soaking to obtain β-silicon nitride whiskers.

3. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 2, characterized in that: In the step of preparing β-silicon nitride whiskers, The mass ratio of silicon powder, α-Si3N4 and Y2O3 is 70-80:20-30:2.5-3; The particle size of the silicon powder is 300-500nm; The particle size of the α-Si3N4 is 500-800nm; The concentration of the hydrofluoric acid solution is 5-10wt%.

4. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 1, characterized in that: In the step of modifying the β-silicon nitride whiskers, the mass ratio of the β-silicon nitride whiskers, the hydrolysis-activated polyacrylamide solution, and the N,N-dicyclohexylcarbodiimide is 10:50-70:0.2-0.

4.

5. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 1, characterized in that: In the step of modifying the β-silicon nitride whiskers, the preparation method of the hydrolysis-activated polyacrylamide solution is as follows: dissolving polyacrylamide in water to prepare a polyacrylamide solution, dripping a NaOH solution into the polyacrylamide solution under stirring, stopping the dripping when the pH value of the solution reaches 10-11, heating the mixed solution to 60-80° C., stirring and reacting at a constant temperature for 1-2 hours, and controlling the pH range of the solution to be 10-11 during the reaction, and obtaining a hydrolysis-activated polyacrylamide solution after the reaction is completed.

6. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 5, characterized in that: The number average molecular weight of the polyacrylamide is 1.06-2.11 million; The concentration of the polyacrylamide solution is 5-8wt%; The concentration of the NaOH solution is 20-30 g / L.

7. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 1, characterized in that: In the step of preparing the silicon nitride composite powder, The mass ratio of water, methacrylamide, α-Si3N4 powder, Y2O3, MgSiN2, dispersant, and modified β-silicon nitride whisker is 100:8-10:100-120:3-4:3-4:0.6-1:6-8; The dispersant is one of sodium polyacrylate and polyvinyl alcohol.

8. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 1, characterized in that: In the step of preparing the silicon nitride composite powder, The frequency of the primary ultrasound is 50-70kHz; The frequency of the secondary ultrasound is 20-30 kHz.

9. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 1, characterized in that: The cold isostatic pressing method comprises pressing the silicon nitride composite powder at a pressure of 110-130 MPa for 30-35 minutes to obtain a silicon nitride ceramic blank.

10. The method for preparing a high thermal conductivity silicon nitride ceramic material for lightning protection insulators according to claim 1, characterized in that: The gas pressure sintering method is to put the silicon nitride ceramic blank into a gas pressure sintering furnace, and sinter it at 1800-1900° C. and 3-4 MPa nitrogen pressure to obtain high thermal conductivity silicon nitride ceramic.

Citation Information

Patent Citations

  • Preparation method of silicon nitride ceramic substrate

    CN112573936A

  • Preparation method of silicon nitride whisker

    CN101864620A

  • Method for preparing beta-silicon nitride whisker through simple phase change control

    CN107164803A

  • Bionic silicon nitride ceramic material and preparation method thereof

    CN111620711A

  • Method for preparing high-toughness high-temperature-resistant directionally-arranged silicon nitride monolithic porous ceramic

    CN114804912A